SPECIFICS OF QUALITY ASSESSMENT OF CORPORATE GOVERNANCE IN MEDIUM-SIZED COMPANIES WITH STATE PARTICIPATION - I. N. Tkachenko (Стратегические решения и риск-менеджмент)
The aim of the study is to identify the specific characteristics of companies with state participation, relating to medium-sized companies, and their reflection during assessment of corporate governance quality in preparation for the long-term development programs for public companies, the share of the Russian Federation in the authorized capital in the aggregate more than fifty per cent. Actualization of the goal set in this publication is that the typical structure of corporate governance of large corporations is of little use for small and medium-sized companies because of their significant features. It occurs sort of collision: the corporate governance system in mid-sized companies can not be possesses a fundamental corporate governance of large corporations, but it should be oriented towards the development and improvement. After all, only the use of basic standards, elements and tools of traditional corporate governance systems allows to build robust governance structure to medium-sized businesses.The article discusses specific features of corporate governance and to assess its quality with regard to medium-sized companies with state participation. Spells out interests of stakeholders associated with the company. The problems of corporate governance in the midmarket companies with 100% state package are analyzed. We consider the practical experience of evaluating the quality of corporate governance for the purposes of long-term development of the company and strategic management. Consideration characteristics companies with state participation, belonging to medium-sized businesses, during of corporate governance quality assessment in them will expand methodological assessment base and can be used in the practice of taking effective managerial decisions.